Tishreen University contribution to the development and modernization of higher education system in the Syrian Arab Republic between 2000 and 2010 - Hassan, Maysoun (Latakia University Journal - Arts and Humanities Sciences Series, 2018)
Tishreen University is one of the main pillars in the development and modernization of the higher education system in the Arab Republic for its importance in progress and development, in intellectual and developmental construction and its reflection on society and its various institutions. Tishreen University has achieved many successes towards development and modernization with policies of expanding education, With the scientific, technological and cognitive revolution, in increasing the number and spread of universities and colleges. The research aims to study the extent to which Tishreen University contributed to the development and modernization of the higher education system in the Syrian Arab Republic between 2000 and 2010 through studying the reality and development of higher education in Tishreen University in a descriptive and analytical study during the period 2000-2010. The Ministry of Higher Education, the Directorate of Planning and Statistics, the State Planning Authority, the calculation of some educational indicators, and the calculation of the general trend equation of the relationship between the number of first-year students and the time at Tishreen University to measure the average growth and growth during the study period 2000-2010. The year 2020. D. Study and Analysis The research results in the following results: • The total number of students in the first stage increased annually by 1722 students, an average increase of 5.61% during the period 2000-2010 and will increase annually on average by an average increase of /4.1 / The number of students and time is a very positive and strong relationship, and the relationship between the number of students graduating and time is very positive and strong. • The proportion of new students to the total number of students in the first university is increasing during the period 2001-2002, and then decrease by the year 2007, as it increases in 2008, and returns and decreases in 2009, and then increasing in 2010 .. • . The research proposals should coordinate between the higher educational leadership, whether in the Ministry of Higher Education or the universities, on the issue of improvement and continuous development of the education process in a manner that keeps abreast of the changes and modern developments, and taking different perspectives in the planning process (labor market needs, students, And then move towards crystallization and employment in the development of higher education